GO/CNT−OH/Nafion Nanocomposite Humidity Sensor Based on the LC Wireless Method - Chengkai Wang; Chunxiao Jiao; Meng Wang; Jinghong Pan; Qi Wang (Nanomaterials, 2023)
In recent years, LC resonant sensors have gained widespread attention for their extensive applications in industries such as pharmaceutical storage and food transportation. A wireless passive sensor with a good sensing performance is proposed based on a GO/CNT−OH/Nafion nanocomposite. The sensor was fabricated via inkjet printing technology, and the surface morphology of the GO/CNT−OH/Nafion nanocomposite was characterized by SEM measurement. It is found that the MWCNTs support the GO layer and the hydrophobic chains of Nafion interact with the hydrophobic layer of GO, resulting in a larger cavity and hydrophilic surface of the entire material. This structure well reflects the fact that the mixing of MWCNTs and Nafion provides the entire material with a stronger water absorption. The experimental study shows that the proposed humidity sensor has a frequency variation of 103 kHz/%RH at low humidity (30–60% RH) and a sensitivity of 931 kHz/%RH at high humidity (60–95% RH), while the sensitivity value from 30–95% RH is 547 kHz/% RH. The response time and recovery time are 110 s and 115 s, respectively. In addition, the tests showed that the GO/CNT−OH/Nafion nanocomposite applied to the humidity sensor had a maximum humidity hysteresis of about 3% RH at 30–95% RH, the resonant frequency remained basically unchanged after 50 h of testing, and the whole sensor possessed a good stability. After conducting several repeated experiments, it was found that the resonant frequency error of the whole sensor was low and did not affect the overall sensing test, which proved the reproducible preparation of the sensor. Finally, the humidity-sensing mechanism of the proposed sensor was analyzed in this paper, and it was found that GO enhanced the hygroscopic properties of GO/CNT−OH/Nafion nanocomposite when it was supported by MWCNT-OH and included uniformly dispersed Nafion. Therefore, our proposed humidity sensor is suitable for humidity detection above 30% RH in both sealed and open environments.